The Therapeutic Collaboration in Life Design Counselling: The Case of Ryan - Taveira, Maria do Céu (2018)
This study examined the therapeutic collaboration in a case of Life Design Counseling (LDC) with narrative change and positive career outcomes. The therapeutic collaboration-change model and correspondent coding system were used to in-tensively study the helping relationship throughout three sessions of LDC. The collaboration coding system enables the assessment of each therapeutic exchange within and outside of the client’s therapeutic zone of proximal development, defined as the space between the client’s actual therapeutic developmental level and his/her potential developmental level fomented by a collaborative relationship. Results show that in all sessions, counsellor and client worked mainly within the therapeutic proximal development zone, that is, they were able to interact collaboratively. The coding of the counsellor’s interventions throughout the counselling process was in accordance with the life-design framework. The collaboration-change model and coding system contributed to understand the process of change in LDC.